Multidimensi Kualitas Pelayanan Perawat Terhadap Kepuasan Pasien - Basirun Al Ummah; Alamiarty Dyah Suminar; Teguh Al Wobowo (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Background, the quality of service is important by looking at the various dimensions of a person's needs. Multidimensional quality of service is important in nursing care services, many similar studies have been carried out, but this dimension emphasizes the dimensions that are fundamental to patient satisfaction. The purpose of this study was to see the effect of the dimensions of reliability, responsiveness, assurance, tangibility, empathy on patient satisfaction. Research Methods, the method of this research is descriptive quantitative with cross sectional approach, sampling by accidental sampling, the number of samples is 43 patients, the measuring instrument used is a questionnaire and is valid with a significance value <0.05 and the reliability test results state the data in this study is reliable. with a Chronbach Alpha value of 0.983 (> 0.60). Results and analysis of the discussion, namely; 1) there is an effect of reliability dimensions on patient satisfaction, this is based on the results of the analysis test with a significance value of 0.00 (p <0.05), which means that the reliability dimension increases responsiveness satisfaction increases patient satisfaction 3) there is an effect of assurance on patient satisfaction, the results of the analysis test with a significance value of 0.00 (p <0.05), which means that the assurance dimension increases patient satisfaction 4) there is a tangible effect on patient satisfaction, based on the results of the analysis test with a significance value of 0.00 (p <0.05) , which means tangible increases patient satisfaction and 5) there is an effect of empathy on patient satisfaction, based on the results of the analysis test with a significance value of 0.00 (p <0.05), which means that empathy is able to increase patient satisfaction. Conclusion, dimensions of reliability, responsiveness, assurance, tangible, empathy in patient care services can increase patient satisfaction. The service department must emphasize this service to provide satisfaction to patients. Keywords; Quality, service, satisfaction